Role of glutamate dehydrogenase in ammonia assimilation in nitrogen-fixing Bacillus macerans. - Kanamori, K (1987)
Pathways of ammonia assimilation into glutamic acid in Bacillus macerans were investigated by measurements of the specific activities of glutamate dehydrogenase (GDH), glutamine synthetase, and glutamate synthase. In ammonia-rich medium, GDH was the predominant pathway of ammonia assimilation. In nitrogen-fixing cells in which the intracellular NH4+ concentration was 1.4 +/- 0.5 mM, the activity of GDH with a Km of 2.2 mM for NH4+ was found to be severalfold higher than that of glutamate synthase. The result suggests that GDH plays a significant role in the assimilation of NH4+ in N2-fixing B. macerans.